Features of resolving legal issues of personal relationships between parents and children on the Law of the Kyrgyz Republic (Journal of actual problems of jurisprudence, 2018)
This article clarify the features of resolving legal problems of personal relations between parents andchildren and are based on the analysis conclusions.Keywords: protection of the rights of the child; parents and children; family; non-property rights of minors;trustees and trustees; child care facilities.